Achieving Economic Development in the Era of Globalization - Sharma, Shalendra D. (New York Routledge, 2008)
Challenging assumptions about the benefits of specific development practices, this book provides readers with overview of how competing frameworks have developed and the ways that specific development practices reflect specific understandings of the main debates, as well as offering a comprehensive historical overview of attempts to achieve economic development.
Includes bibliographical references (p. [164]-192) and index.
Keywords: Economic development--Effect of globalization on